The influence of decentralization on formation of local budgets in Ukraine - Goraj, A. (Land Management, Cadastre and Land Monitoring, 2018)
Abstract. For today, the main development of a democratic state is to ensure the improvement of the well-being of each individual citizen.Having analyzed the experience of the developed European countries, achievement of this goal is possible only in the conditions of high-quality public administration, which strengthens democratic institutions, eliminates the inequality of access to public goods, improves the quality of public services and the standard of living of the population.At the present stage, Ukraine, in accordance with the basic provisions of the European Charter of Local Self-Government, continues to focus its efforts on the implementation of the European integration course on the development of local and regional democracy. And decentralization itself is, today, one of the most successful reforms that is being implemented effectively in the country.In the context of reforming the public finance system, a tendency towards decentralization in public administration is relevant, as a result of which a certain number of powers are transferred to the local authorities.Thus, financial decentralization can balance the mechanisms of providing public services with the needs and preferences of local communities.Keywords. Local government, decentralization, budget, local budget, finance, local budget revenues, budget decentralization.